Collaborative Newsroom of Local Journalists in Investigative Coverage on Online Media - Rani Dwi Lestari; Ana Nadhya Abrar; Md. Shahidul Haque (Komunikator, 2024)
Investigative reporting in the digital era faces challenges due to the presence of online and social media. Long reporting times, limited budgets, and minimal editorial resources increasingly undermine the sustainability of investigative journalism. The competition for rapid news coverage further pressures investigative reporting. Several journalists in Yogyakarta and other regions address these challenges by practicing collaborative journalism through collaborative newsrooms. This research aims to describe how journalists in the field use collaborative newsrooms to produce investigative reports. It explores collaborative journalism practices as a middle ground to deliver credible, public-interest reporting using data and investigative journalism principles. The study employs a case study method, involving in-depth interviews with journalists and the analysis of published news data. The findings show that journalists in Yogyakarta use a temporary and separate model for their collaborative newsrooms, focusing on short-term collaboration on a single topic. These newsrooms leverage technology to facilitate communication and data sharing. Tasks are divided among participants to ensure comprehensive, in-depth, data-driven reporting. The reports are published in online media, serving as a strategic approach to presenting investigative journalistic work often constrained by limited media space.